Clinical and Molecular Features of Early Infantile Niemann Pick Type C Disease - Seker Yilmaz, Berna (Int J Mol Sci, 2020)
Niemann Pick disease type C (NPC) is a neurovisceral disorder due to mutations in NPC1 or NPC2. This review focuses on poorly characterized clinical and molecular features of early infantile form of NPC (EIF) and identified 89 cases caused by NPC1 (NPC1) and 16 by NPC2 (NPC2) mutations. Extra-neuronal features were common; visceromegaly reported in 80/89 NPC1 and in 15/16 NPC2, prolonged jaundice in 30/89 NPC1 and 7/16 NPC2. Early lung involvement was present in 12/16 NPC2 cases. Median age of neurological onset was 12 (0–24) and 7.5 (0–24) months in NPC1 and NPC2 groups, respectively. Developmental delay and hypotonia were the commonest first detected neurological symptoms reported in 39/89 and 18/89 NPC1, and in 8/16 and 10/16 NPC2, respectively. Additional neurological symptoms included vertical supranuclear gaze palsy, dysarthria, cataplexy, dysphagia, seizures, dystonia, and spasticity. The following mutations in homozygous state conferred EIF: deletion of exon 1+promoter, c.3578_3591 + 9del, c.385delT, p.C63fsX75, IVS21-2delATGC, c. 2740T>A (p.C914S), c.3584G>T (p.G1195V), c.3478-6T>A, c.960_961dup (p.A321Gfs*16) in NPC1 and c.434T>A (p.V145E), c.199T>C (p.S67P), c.133C>T (p.Q45X), c.141C>A (p.C47X) in NPC2. This comprehensive analysis of the EIF type of NPC will benefit clinical patient management, genetic counselling, and assist design of novel therapy trials.